Development Of Wideband Power Amplifier For RF/Microwave Front-End Subsystem - Zakaria, Zahriladha; Muhamad Fadzil, Muhamad Fadhli; Othman , Abdul Rani; Salleh, Azahari; Awang Md Isa, Azmi; Haron, Nor Zaidi (Penerbit UTM Press, 2014)
-